Managing economic crisis in Southeast Asia - International Conference on Managing Economic Crisis in Southeast Asia (2010 : Singapore?); Saw, Swee-Hock, 1931-; Institute of Southeast Asian Studies.; Saw Centre for Quantitative Finance (Singapore, SI. : Institute of Southeast Asian Studies : Saw Centre for Quantitative Finance, 2011)
Includes bibliographical references and index.